Target Enzyme Activity and Phosphorylation of Pathway Molecules As Specific Biomarkers in Transplantation. (April 2016) - Budde, Klemens; Sommerer, Claudia; Rissling, Olesja; Dieterlen, Maja T.; Barten, Markus J.
Abstract : Abstract: Therapeutic drug monitoring of immunosuppressants in the clinic is based on the measurement of blood concentration (pharmacokinetics). However, pharmacokinetic monitoring of immunosuppressants does not allow prediction of individual differences in pharmacological effects on immune cells. Pharmacodynamic (PD) monitoring via direct determination of target enzyme activity and phosphorylation of pathway molecules may enhance therapeutic drug monitoring and allow prediction of individual responses to immunosuppressants. This review discusses the clinical relevance of monitoring the activity of inosine-5′-monophosphate dehydrogenase (IMPDH), the target enzyme of mycophenolic acid, and of the phosphorylation of mechanistic target of rapamycin (mTOR) molecules. Significant progress regarding a robust and practicable assay for the determination of IMPDH activity as a specific PD parameter of mycophenolic acid activity has been achieved. The development of a rapid and reliable IMPDH assay system suitable for use in clinical practice was an important step that allowed thorough pharmacokinetics–PD investigations in large numbers of mycophenolic acid–treated patients. A reproducible and validated IMPDH assay was used in a few clinical trials by different research groups and is based on the chromatographic determination of newly generated xanthine monophosphate in mononuclear cell lysates. This assay requires only small volumes of blood and can be reliably used in multicenter trials; however, more clinical data from larger cohorts are needed to determine its clinical utility. Regarding monitoring of mTOR inhibitors (mTORis), the results of the first study that provided data on measurement of mTOR pathway molecules [p70 ribosomal protein S6 kinase (p70S6 kinase) and phosphorylated ribosomal protein S6] suggest that they are suitable targets for individualized PD monitoring of sirolimus and everolimus after organ transplantation. At present, only the phospho-flow phosphorylated ribosomal protein S6 assay has been validated in vitro and evaluated for confounding factors in vivo. The reported specific biomarkers for IMPDH activity and phosphorylation of mTOR molecules must be validated in clinical settings and multicenter studies to prove their clinical validity.